COLLABORATIVE FILTERING AS ONE OF THE MAIN METHODS OF CONTENT RECOMMENDATIONS: MAIN PROBLEMS AND WAYS TO SOLVE - Івохін, Євген; Шелякін, Гліб (Modern engineering and innovative technologies, 2024)
The article considers collaborative filtering as one of the main methods of content recommendation. The main problems of the method are analyzed, such as "synonymy of objects", "cold start", sparsity of data. The ways to solve these problems by using the